Механізм формування облікової політики банків - Андренко, Олена Анатоліївна; Мордовцев, Олександр Сергійович (Харківський національний університет міського господарства ім. О. М. Бекетова, 2017)
Досліджено механізм формування облікової політики банку: визначено цілі, завдання, принципи, основні етапи, відображено організаційний, методологічний й конструктивний аспекти Положення про облікову політику. Наведено перелік основних статей облікової політики, які характеризують основні напрямки діяльності банків. Описано основні методи оцінки активів та зобов'язань, в тому числі в іноземній валюті.

The purpose of the article is to develop a mechanism for the formation of the accounting policy in Ukrainian banks. The mechanism determines the goals, objectives, principles, functions, and stages of the formation and implementation of the accounting policies. The accounting policy of the bank is a goal-directed organizational and management activity, the purpose of which is to ensure the use of methods, principles, rules and accounting procedures; to provide the regulatory status to independently developed methods of accounting; to increase the efficiency of accounting. The first stage involves the development and systematization of the main components of the accounting policy in accordance with the established regulatory norms and methodological recommendations. At the second stage, it is proposed to use the approach according to which the structure of the Regulation on the bank's accounting policy is determined by the organizational, methodological and constructive aspects of the accounting policy. Within the organizational component of the Regulations, the organizational structure of the accounting service is determined; the rules are established for the distribution of responsibilities and powers of responsible people when conducting accounting operations; the rules for document circulation and information processing technologies using information technologies are approved; the order of mutual settlements between the branches and other divisions of the bank is approved. The methodological aspect involves the development of methods for the valuation of assets, liabilities, and separate reporting items, as well as the procedure for recording the main operations of the bank and accounting for the settlements of the head bank with the branches. The paper gives a brief description of the methods for assets and liabilities valuation. The constructive aspect involves the development and approval of a work plan for synthetic and analytical accounts; primary documents, forms and reports for internal use, the procedure for the inventory of financial assets, property and tangible assets. At the implementation stage, it is important to organize control over the implementation of the accounting policy with the establishment of feedback, which will, if necessary, timely correct the Regulations.
Mechanism for the formation of accounting policy in banks
Keywords: облікова політика; облік; банки; методи оцінки активів та зобов'язань; accounting policy; accounting; bank; methods for valuation of assets and liabilities